2023
DOI: 10.1186/s12905-023-02158-w
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of breast self-examination practice among women attending pastoralist health facilities, Southern Ethiopia: a cross-sectional study

Abstract: Background Breast cancer remains the most serious public health problem affecting millions of women worldwide. Despite various studies regarding breast self-examination practices conducted among health professionals and students in Ethiopia, limited information was found on women attending health care services in the pastoralist community. This study aimed to identify the determinants of breast self-examination practice (BSE) among women attending pastoralist health facilities in Southern Ethio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The samples from all these research studies, including the present study, are from rural regions where various psychosocial and demographic factors are associated with carrying out BSE. They include education, area of residence, awareness about BSE, family history with breast cancer [ 30 ], health professionals’ advice on BSE, ethnicity [ 42 ], and employment [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples from all these research studies, including the present study, are from rural regions where various psychosocial and demographic factors are associated with carrying out BSE. They include education, area of residence, awareness about BSE, family history with breast cancer [ 30 ], health professionals’ advice on BSE, ethnicity [ 42 ], and employment [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy is another variable determining whether women engage in BSE [ 32 ]. Socio-demographic aspects such as education and domicile also relate to BSE [ 30 ]. In addition, culture was found to influence self-care behaviours in general [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…An institutional-based cross-sectional study conducted among young adults attending family planning services revealed that 224 (53.2%) women believed that it would be simple to perform BSE, 293 (69.6%) women mentioned that BSE was not a sexual activity initiation, 179 (42.5%) women reported that it was inappropriate to touch their breasts, 73.9% women said that BSE is important for preventing breast cancer and 59.4% women want BSE because it does not result in a positive cancer test ( 20 ). The systematic scoping review that included 21 studies revealed that the majority of senior high school students in Nigeria (82.6%) and female nurses in Ghana and Ethiopia (59.2%) had positive attitudes toward BSE ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Northwest Ethiopia in 2021 revealed that 17.4% of students studied had practiced BSE, which is associated with a lack of knowledge ( 22 ). Furthermore, the study among women attending family planning in southern Ethiopia revealed that 89 (21.1%) women have ever engaged in BSE, while 192 (57.8%) women have never practiced BSE because they believed they were healthy and others were afraid to be diagnosed with breast cancer ( 20 ). Meanwhile, the study in Turkey reported that 50% of students said they had performed BSE, and 33.3% reported having done so regularly.…”
Section: Discussionmentioning
confidence: 99%